Inovasi Teknologi Pemanas Kumparan sebagai Solusi Berkelanjutan dalam Proses Pembakaran Bata untuk Mengatasi Dampak Lingkungan Negatif - Masri; Suhaeri; Noviana, Dwi; Azhar (Journal of Engineering and Science, 2023)
This research aims to design and develop coil heater technology as an alternative heat source to replace wood in the brick-firing process. The research methodology involves the design of an efficient and environmentally friendly coil heater and its implementation in the brick production process. In this study, the performance of the coil heater is analyzed to ensure that the generated heat is sufficient for the brick-firing requirements. The research findings indicate that coil heater technology is capable of providing the necessary heat to achieve optimal temperatures in the brick-firing process. Furthermore, the use of this coil heater technology successfully reduces dependence on wood as the primary fuel source. The implementation of coil heater technology in the brick-making industry is expected to make a positive contribution to the environment and the sustainability of natural resources. This research stimulates innovation in the development of alternative technologies that can reduce carbon footprints and improve the overall efficiency and sustainability of brick production processes.